POTRET MASYARAKAT URBAN DALAM NOVEL RESIGN KARYA ALMIRA BASTARI - Anggraini, Meta; Hayati, Yenni (Jurnal Bahasa dan Sastra, 2019)
This study aims to: (1) describe the description of the prestige of urban recreation in Almira Bastari's Resign novel; (2) describe the description of the instant life culture of urban communities in Almira Bastari's Resign; (3) describe the description of the virtual lifestyle of urban communities in Almira Bastari's Resign; (4) describe the description of the individualist lifestyle of urban society in Almira Bastari's Resign novel. This type of research is qualitative research using descriptive methods. Based on the results of data analysis obtained; (1) the recreational prestige of urban community leaders in Almira Bastari's Resign includes education, employment, entertainment venues visited, and restaurants visited; (2) the instant life culture of urban communities depicted in Almira's Resign in general coming to fast food restaurants; (3) the individualist lifestyle of urban society in Almira Bastari's Resign as if it had never been separated from technology and communication in everyday life. Urban communities rely on information and communication technology to seek information, communicate, and obtain entertainment; (4) a portrait of the lifestyle of the individual urban society in Almira Bastari's Resign, like to do everything by yourself and some people prefer to live without the interference of othersKeywords: urban society, Resign novel, Almira Bastari